2023
DOI: 10.1002/hlca.202200160
|View full text |Cite
|
Sign up to set email alerts
|

Structural Flexibility of Metal Chelate Complexes and Its Relation to Supramolecular Chemistry

Abstract: This article is in memory of Professor Jack D. Dunitz, whose laboratory I visited in 1979. I hope I have passed on to my own students some of the ideas and inspiration that Jack gave so generously.Crystal structures of metal chelate and related complexes in the Cambridge Structural Database have been analyzed, with respect to their use as components in supramolecular metal-organic compounds. In β-diketonate complexes, the distribution of angles between ligands is relatively broad; other ligands, such as 2,2'-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…In our previous work with copper molecular squares (Figure ), only squares (Cu 4 L 4 ) were formed, rather than the hexagons (Cu 6 L 6 ) that were expected based on the angle of ca. 120° between the β-diketonates. , Thus, β-diketonates are somewhat flexible in the way they bind to Cu 2+ ; we have recently shown that metal β-diketonates are among the most flexible among common chelates in their coordination geometry …”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In our previous work with copper molecular squares (Figure ), only squares (Cu 4 L 4 ) were formed, rather than the hexagons (Cu 6 L 6 ) that were expected based on the angle of ca. 120° between the β-diketonates. , Thus, β-diketonates are somewhat flexible in the way they bind to Cu 2+ ; we have recently shown that metal β-diketonates are among the most flexible among common chelates in their coordination geometry …”
Section: Introductionmentioning
confidence: 97%
“…37,38 Thus, β-diketonates are somewhat flexible in the way they bind to Cu 2+ ; we have recently shown that metal β-diketonates are among the most flexible among common chelates in their coordination geometry. 42 The new supramolecular complexes do not form crystals suitable for X-ray analysis; also, their mass spectra do not provide useful information concerning the size of the molecules formed. In this work, we use atomic force microscopy (AFM) and analytical ultracentrifugation (AUC) to provide additional information about the structure of the new supramolecular Cu(II) complexes.…”
Section: ■ Introductionmentioning
confidence: 98%
See 1 more Smart Citation